PEMANFAATAN EKSTRAK DAUN CENGKEH (Syzigium aromaticum) SEBAGAI REPELLENT NABATI DALAM MENGURANGI JUMLAH LALAT YANG HINGGAP SELAMA PROSES PENJEMURAN IKAN ASIN - Minar Indriasih; indra cahaya; Taufik Ashar (Lingkungan dan Kesehatan Kerja, 2013)
The Utilization of clove leaf (Syzigium aromaticum) extract to reduce the flies’ infestation during the salted fish-drying process. Insecticide residues contained in food chain can give negative effects on public health. Various studies have shown that insecticide residues were contained in salted fish products by the application of synthetic insecticides on the fish to avoid flies infestation during the drying process. The aim of this study was to determine the application of clove leaf (Syzigium aromaticum) extract to reduce flies’ infestation during the drying process. The design of this research was quasi-experimental with Completely Randomized Design (CRD), conducted with six different concentrations of the extract which were 0% (as control), 2.5%, 5%, 7.5%, 10%, 12.5 % in three replications.The data were analyzed using One Way Anova or Kruskall Wallis, and continued with Tukey HSD test. The results of this study indicated that the flies’ species which infested fish during the drying process were Musca domestica and Chrysomya megacephala. The protection power of clove leaf (Syzigium aromaticum) extract to flies on concentration 2,5% was 32,59%, on concentration 5% was 44,07%, on concentration 7,5% was 50,74%, on concentration 10% was 94,44%, on concentration 12,5% was 98,14%. The conclusion was clove leaf (Syzigium aromaticum) extract on concentration 10 % was the most effective to avoid flies’ infestation during the drying process. Hopefully, clove leaf (Syzigium aromaticum) extract can be use as one of the controller alternatives upon the vector especially for the flies and it is also use as natural insecticide which is safe for both environment and human. Keywords: clove leaf (Syzigium aromaticum), natural repellent, flies, salted fish